The European Social Model and eastern enlargement - Friedrich Buttler; Ulrich Schoof; Ulrich Walwei (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
The European Social Model (ESM) is increasingly becoming a model of integration policy. The idea is based on a combination of economic efficiency, in the sense of high productivity, competition and economic growth, and a high level of employment on the one hand together with social cohesion on the other hand. At the same time the ESM is understood as a dynamic model in evolution, whose development is influenced by global, European and national processes, including eastern enlargement. With the accession of the eight Central and Eastern European countries to the European Union, the economic and social disparities between the now 25 EU Member States have grown considerably. On the basis of theoretical and empirical literature this paper develops answers to the following questions in particular: will there be a gradual erosion of the ESM, are there prospects of convergence or are new vectors developing in the enlarged field of power? The authors reach the conclusion that the old and the new Member States, starting out from different historical experiences in the past decades and different levels of production and productivity, will have to withstand structurally similar challenges in the foreseeable future if they wish to achieve economic efficiency and social cohesion simultaneously. From the perspective of the new Member States, which come from an egalitarian tradition, there is every reason to believe that the majority of the population desires social cohesion and will demand it. Together with the diverse integration advantages of enlargement, a successful catching-up process in the new Member States provides good preconditions for the preservation and productive development of the ESM.
Keywords: 330; EU-Osterweiterung; regionale Disparität; europäische Sozialpolitik; europäische Integration; Konvergenz; Arbeitsmarktentwicklung; Wirtschaftsentwicklung; Produktivitätsentwicklung; soziale Integration; Integrationspolitik; Leitbild; Europäische Union; Osteuropa; Mitteleuropa